CLINICAL AND MORPHOLOGICAL APPROACH TO DIAGNOSIS OF "IDIOPATHIC" ARRHYTHMIAS AND DILATED CARDIOMYOPATHY SYNDROME AS A BASIS FOR DIFFERENTIATED THERAPY. Part II (Treatment) - O. V. Blagova; A. V. Nedostup; E. A. Kogan; V. A. Sulimov; Yu. V. Osipova; V. P. Sedov; A. G. Kupriyanova; V. A. Zaydenov; A. E. Donnikov; V. V. Kadochnikova (Рациональная фармакотерапия в кардиологии)
Part I (Diagnostics), was published in the journal “Rational Pharmacotherapy in Cardiology” 2014;10(1):62-72Aim. To develop a comprehensive clinical and morphological approach to the nosological diagnosis and treatment of "idiopathic" arrhythmias (IA) and the syndrome of dilated cardiomyopathy (DCM).Material and methods. Patients (n=320) with IA (n=190; 117 women, age 45.3±14.8 years) and DCM (n=130, 41 women, age 46.9±12.5 years) were included in the main group. 51 people (patients with ischemic heart disease; heart valve disease, hypertrophic cardiomyopathy, who underwent open-heart surgery; healthy volunteers) were included in the control group. Along with the standard tests evaluation of the level of anti-heart antibodies (185 patients with IA and 122 with DCM), viral serology (166 and 122), multispiral computed tomography (42 and 88), cardiac magnetic resonance imaging (41 and 22), coronary angiography (19 and 54), myocardial biopsy/autopsy (19/0 and 33/9) were performed.Results. According to morphological study infectious-immune myocarditis was found in 78.9% patients with IA and 66.7% patients with DCM, arrhythmogenic right ventricular dysplasia in 5.3% and 4.8% of patients, respectively. Other genetic cardiomyopathies, including combination with myocarditis were revealed in other patients. The frequency of the viral genome detection in the myocardium in IA, DCM and the control group was 17.6%, 66.7% and 77.1%, respectively. However in the control group the incidence of myocarditis and anti-heart antibodies titers were significantly lower than in the main group, where a strong correlation between myocarditis and anti-heart antibodies titers was found. The algorithm of noninvasive nosological diagnostics was developed; it allowed to verify diagnosis in 95% of IA patients and 89% DCM patientsThe basic therapy (antiviral drugs, corticosteroids, hydroxychloroquine, azathioprine) was performed in some patients with myocarditis. Improving of the antiarrhythmic effect of treatment in patients with IA, a significant increase in ejection fraction, a reducing of the size of the heart chambers and of pulmonary artery pressure in patients with DCM, a reducing of the need in surgical treatment (including in the virus-positive patients) occurred as results of treatment.Conclusion. Nosological cause of IA and DCM syndrome can be diagnosed in most patients by using an integrated clinical and morphological approach. This allows managing effective etiotropic and pathogenetic treatment.